Applicability of non-structural English instruction in foreigners and taxi drivers’ interaction (2016)
This research is framed within the qualitative paradigm with a descriptive and explanatory perspective. Its main focus was on analyzing the applicability of using non-structural English to a group of taxi drivers who frequently transported foreigners in Bogota city. Two major instruments of collecting data were designed and used: an interview for foreigners who live in Bogota and a survey for taxi drivers to elicit their opinions. The collected data were analyzed and allowed to create an analysis matrix that triangulated the information, taking into account the relevance of the results obtained it was suggested the use of an non-structural English as a communication tool between taxi drivers and foreigners and economic development. Furthermore this research yielded information about taxi driver's job, since often they are the first contact for foreigners who visit the city, besides it was evident the necessity to speak English to increase their income and provide better service that allows easy and assertive communication, qualifying the profession of taxi drivers in Bogota.